Unveiling the power of enablers in enacting sustainable supply chain management practices - Mohammad Abdul Jabber; Mohammad Thoufiqul Islam; Tanjil Hossain; Razia Sultana (Cleaner Logistics and Supply Chain)
With the contemporary environmental challenges driven by global warming, industries must prioritize aligning their business operations with responsibilities toward society, environment, and economy, emphasizing the crucial role of enablers in facilitating the adoption of Sustainable Supply Chain Management (SSCM), particularly in emerging economies. While previous studies mostly identified the SSCM enablers and found out their association with each other, however, to address this gap, this study aims to explore the influence of the enablers (policy, technology, environment, finance, and human resource) on the adoption of SSCM using Diffusion of Innovation (DOI) theory as a theoretical lens in the context of a developing economy by Structural Equation Modelling (SEM) approach. The findings suggest that policy and the environment category enablers significantly influence the adoption of SSCM. Insufficient funds and lack of academic and training resources pertaining to the supply chain, the influence of technology, finance, and human resource enablers are found to be non-significant, particularly in the developing country context. This research contributes to sustainability literature by providing empirical evidence on the influence of enablers in SSCM adoption, offering valuable guidance to supply chain managers and regulatory bodies for formulating effective strategies and policies.